Aspek Spasial Kesesuaian Penggunaan Lahan Daerah Aliran Sungai (DAS) Wanggu Hulu Menggunakan Citra Landsat-9 dan Sistem Informasi Geografis - Tahir, Tahir; Yusuf, Daud (Innovative: Journal Of Social Science Research, 2024)
Utilizing remote sensing data and Geographic Information Systems to analyze the spatial distribution of watershed land use is one way to prepare land use designations. This research aims to determine the distribution of land use in the Wanggu River Basin District. South Konawe. The method used in this research uses a survey method with supervised classification. Based on the accuracy test (confusion matrix), the accuracy of the Landsat-9 image interpretation results was obtained at 86.63%, the watershed land use is suitable or the interpretation results are in the good category, so that land suitability can be obtained. In the Wanggu watershed, suitable land is more dominant, where suitable land has an area of 43,776. 96 Ha or 67.58%, compared to unsuitable land where unsuitable land has an area of 20,764.79 Ha or 32.42%. The research results obtained eight land use classes, namely, empty land, residential areas, water bodies, shrubs, rice fields, plantations, ponds and forests. The results of the analysis showed that the pond land use class had the smallest percentage, namely 1.09%, while the land use class had the lowest percentage. high, namely forest with a percentage of 64.01%.